Prognostic significance of CUB domain containing protein expression in endometrioid adenocarcinoma - Mamat, Suhana; Ikeda, Jun-Ichiro; Enomoto, Takayuki; Ueda, Yutaka; ., Nur Rahadiani; Tian, Tian; Yi, Wang; Ying, Qiu; Kimura, Tadashi; Aozasa, Katsuyuki; Morii, Eiichi (Spandidos Publications Ltd., 2010)
CDCP1, a transmembrane protein with intracellular tyrosine residues which are phosphorylated upon activation, is supposed to be engaged in proliferative activities and resistance to apoptosis of cancer cells. High level of CDCP1 expression proved to be a poor prognosticator for lung adenocarcinoma. Here, expression level of CDCP1 was immunohistochemically examined in 110 cases (median age of 54.7 years) of endometrioid adenocarcinoma, and its clinical implications were evaluated. Tumor stage was stage I in 71 cases (64.5%), II in 5 (4.5%), III in 28 (25.5%), and IV in 6 (5.5%). Staining intensity of tumor cells was divided into two categories; tumor cells with no to weak and moderate to strong membrane staining. The intensity of CDCP1 expression in each case was defined by the staining of major population of cells as follows; cases with tumor cells showing no to weak and moderate to high membrane staining were categorized as CDCP1-low and CDCP1-high, respectively. Eighty-seven of 110 cases were categorized as CDCP1-high, and the remaining as CDCP1-low. Significant positive correlation was observed between low CDCP1 expression and stage (p=0.0091), relapse rate (p=0.0017), and poor prognosis (p=0.0009). Multivariate analysis revealed that low CDCP1 and advanced stage were independent poor prognostic factors for both OS and DFS. As compared to cancer cells, normal endometrium continuously expressed CDCP1. These suggested that the attitude of CDCP1 in cancers of lung and endometrium was different. Different role of CDCP1 by tissues and cancers is discussed.